PENGARUH PAD DAN DAK TERHADAP BELANJA MODAL DI PROVINSI NUSA TENGGARA TIMUR - Hunggurami, Aldo Alfonsus; Renggo, Yuniarti Reny (Universitas Borneo Tarakan, 2022)
This research aims to determine the Regional Original Income (PAD) and special allocation fund (DAK) on capital expenditures. The subjects in this study were the Regency/City Regional goverments in the province of east Nusa Tenggara in 2017 – 2019. This study used a sample of 21 Regencies and 1 city in east Nusa Tenggara province which were sourced from the Realization Report of the Regional Revenue And Expenditure Budget (APBD) from 2017 – 2019. The data collection technique is by browsing the wesite of the Central Statistics Agency (BPS) of east Nusa Tenggara Province. The data analysis techniqueused is panel data Regression. The results in this study indicate that the Regional Original Income (PAD) and the Special Allocation Fund (DAK), have a positive and significant effect on Capital Expenditures.